2021
DOI: 10.3390/ani11030717
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of in Utero Heat Stress on Carcass and Meat Quality Traits of Market Weight Gilts

Abstract: This study evaluated the impacts of in utero heat stress (IUHS) on the carcass and meat quality traits of offspring when market weight was reached. Twenty-four F1 Landrace × Large White gilts were blocked by body weight and allocated among thermoneutral (IUTN) or IUHS treatments from d 6 to d 59 of gestation. The offspring were raised under identical thermoneutral conditions, and gilts (n = 10/treatment) at market weight (117.3 ± 1.7 kg) were harvested. At 24 h postmortem, the loins (M. longissimus lumborum) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Heat stress alters metabolism, structure and antioxidant mechanisms in skeletal muscle (4). Heat exposure of sows during pregnancy affects foetal development and post-growth carcass quality (3,27). In growing pigs, it has been reported that acute heat stress disrupts muscle redox balance and inflammatory signalling (8,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress alters metabolism, structure and antioxidant mechanisms in skeletal muscle (4). Heat exposure of sows during pregnancy affects foetal development and post-growth carcass quality (3,27). In growing pigs, it has been reported that acute heat stress disrupts muscle redox balance and inflammatory signalling (8,21).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, elevations in environmental temperature also directly alter pigs’ nutrient utilisation, energy metabolism, and hormonal regulation ( 5 , 9 , 24 ). Consequently, heat stress can cause substantial economic losses for the swine industry through its effect on growth rates, carcass composition, sow performance, mortality and morbidity ( 2 , 22 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although fat deposition in fetal/newborn piglets is relatively low, it can be detected in fetal skeletal muscles at mid-gestation [47]. Upregulation of adipogenic transcription factors at early developmental stages potentially programs fetal muscle growth and affects carcass traits of the offspring born to sows experiencing HS during early-mid gestation [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled climate experiments have shown that gestational HS causes lasting effects on the progeny, with reductions in muscle accretion and increased adiposity observed at the finishing stage [9]. Furthermore, sow HS during the first half of gestation contributed to increased subcutaneous fat thickness [10] and decreased loin muscle area in the offspring [11]. A recent study showed that piglets born to sows mated and gestated during summer were lighter at birth, while the carcasses of those born-light progeny tended to deposit less lean and more fat tissue in the loin [12].…”
Section: Introductionmentioning
confidence: 99%